EKSISTENSIRUMAH MAKAN TRADISIONAL TERHADAP MASUKNYA RUMAH MAKAN MODERN DI KOTA BANDA ACEH TAHUN 1980-2016 - Afzalul Zikri; Anwar Yoesoef; Mawardi . (Universitas Syiah Kuala, 2018)
ABSTRACTSince 1980-2017 in the city of Banda Aceh it was continuing to develop. The type of restaurant in Banda Aceh until now consists of traditional and modern restaurants, hence this research entitled